Elaboración de una bebida alcohólica destilada (vodka) a partir de dos variedades de papa chaucha (solanum phureja) y súper chola (solanum tuberosum l.) con alfa amilasa. - Maigualca Pilatasig, Johana Alexandra (2021)
ABSTRACT The preparation of the distilled alcoholic drink vodka was prior to the application of processes for the extraction of starch from two varieties of potatoes (chaucha and super chola), later the must was elaborated to subject it to the alcoholic fermentation process in which two types of yeast (Saccharomyces cerevisiae) in block and powder with alpha amylase respectively for the hydrolysis process. The control and measurement of the pH was carried out daily for a period of 15 days at a fixed time, and ºBrix were controlled every 3 days for the period of 15 days, the initial pH of 4.5 prior to the adjustment with citric acid and 8, 5 ºBrix which was improving the fermentation conditions until finally reaching day 15 with a pH of 3.87 and 6.40 ºBrix. The organoleptic tests carried out on the must of the alcoholic drink resulted in treatment 4 as the best according to the variables of smell, color and flavor. The physicochemical analysis carried out in the laboratory of the best t₄ treatment (potato bean starch + baking powder) results in alcohol, volumetric fraction 4.04% v / v; higher alcohols 55.68mg / 100ml; methanol 0.36 mg / 100 and furfural 0.38 mg / 100ml, these parameters according to the NTE - INEN 369 determine that if the conditions and requirements to be considered an alcoholic drink vodka are met.